Adult Tobacco Cessation in Cambodia: II. Determinants of Intent to Quit. (September 2013) - Tonstad, Serena; Job, Jayakaran S.; Batech, Michael; Yel, Daravuth; Kheam, They; Singh, Pramil N.
Identifying determinants of intent to quit may aid the design of antitobacco programs and promote effective tobacco control policies. In a nationwide survey in Cambodia, two thirds of tobacco smokers and 45% of female smokeless tobacco users planned to stop in the future. Multivariate determinants of intent in 2279 male smokers were age <37 years, age at initiation ≥18 years, Cham versus Khmer ethnicity (odds ratio [OR] = 6.93; 95% confidence interval[CI] = 1.38-34.89), longer education, and professional occupation. In 1188 female smokeless tobacco users, age <25 years, age at initiation ≥18 years, and tuberculosis (OR = 3.26; 95% CI = 1.61-6.61) were associated with intent. In female smokers (n = 321), age 18 to 25 years at initiation was associated with intent. In male smokers and female smokeless tobacco users, perceived physical advantages of tobacco were inversely associated with intent. These findings underscore the importance of policies and interventions to delay initiation and promote cessation in young people and counteract perceived physical benefits.